2021
DOI: 10.1101/2021.02.10.21251508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening for SARS-CoV-2 by RT-PCR: saliva or nasopharyngeal swab? Systematic review and meta-analysis

Abstract: Diagnosis of COVID-19 in symptomatic patients and screening of populations for SARS-CoV-2 infection require access to straightforward, low-cost and high-throughput testing. The recommended nasopharyngeal swab tests are limited by the need of trained professionals and specific consumables and this procedure is poorly accepted as a screening method. The use of alternative validated samples such as saliva is thus much awaited. In order to compare saliva and nasopharyngeal/oropharyngeal samples for the detection … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
1
3
0
2
Order By: Relevance
“…Given the particularly high incidence of COVID-19 in the Nice metropolitan area throughout our study period (incidence between 330 and 720/100,000), our rate of positivity (21-41%) was higher than the rates observed in these 6 cohorts (1.5% to 10.7%). Despite this difference, our NP-OS concordance and the sensitivity of RT-PCR on NP and on OS are in agreement with the results reported for these cohorts; and with the notion of no association between salivary and NP test performance and viral prevalence [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Given the particularly high incidence of COVID-19 in the Nice metropolitan area throughout our study period (incidence between 330 and 720/100,000), our rate of positivity (21-41%) was higher than the rates observed in these 6 cohorts (1.5% to 10.7%). Despite this difference, our NP-OS concordance and the sensitivity of RT-PCR on NP and on OS are in agreement with the results reported for these cohorts; and with the notion of no association between salivary and NP test performance and viral prevalence [19].…”
Section: Discussionsupporting
confidence: 91%
“…RT-PCR on saliva samples has been approved in Japan since June 2020 and in the USA since October 2020. Following the publication of an umbrella review [18] including ten meta-analyses [11,[19][20][21][22][23][24][25][26][27] as well as trials meeting predefined quality criteria, the French "Haute Autorité de Santé" [28] retained very recently the indication of RT-PCR on saliva in the following three situations: 1 / on symptomatic patients as a second-line alternative to NP when NP is difficult or impossible (deviation of the nasal septum, very young patients, patients with psychiatric disorders, etc. ); 2 / on contact persons as a second-line alternative to NP for whom NP is difficult or impossible; 3 / in the first instance as part p. 4 of targeted mass screening, particularly if it is repeated regularly such as in schools, universities, for staff in health care establishments, in nursing homes, etc … From a practical point of view, saliva sampling should be performed more than 30 minutes after the last drink, food, cigarette/e-cigarette, tooth brushing or mouth rinsing [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, there were studies that found lower detection of the virus in saliva when compared to concurrently collected nasopharyngeal swab samples. One meta-analysis of 49 studies found that nasopharyngeal/oropharyngeal swabs had 5% higher sensitivity (92.2%) as compared to saliva (86.7%) [41] . Another study compared the sensitivity of SARS-CoV-2 detection in saliva and concurrently collected nasopharyngeal swab [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Hierbei ist wichtig, dass der Abstrich trotz eines oftmals unvermeidlichen Würgereizes nicht allein aus dem Mundraum oder von der Zungenoberfläche, sondern eben von den bezeichneten Orten genommen wird. Um Abstrichmaterial in Form von anhaftendem Schleim und oberflächlichen Zellanteilen zu bergen, soll der Tupfer einige Sekunden verweilen und mit Wisch-oder Rotationsbewegungen mit der Rachenwand in Kontakt gebracht werden [3][4][5][6][7][8].…”
Section: Rachenabstrichunclassified
“…Der Naseninnenraum wird jedoch nach oben hin wesentlich enger und spaltförmig (rima olfactoria). Der Abstrichtupfer soll etwa 15 s am Ort verbleiben und mehrfach rotiert werden [3,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Rachenabstrichunclassified